The Google Conundrum: Perpetrator or Facilitator on the Net? - Forging a Fair Copyright Framework of Rights, Liability and Responsibility in Response to Search Engine 2.0 - Part II: The Google Books Search Project - CHIK, Warren B. (Institutional Knowledge at Singapore Management University, 2011)
Is Google in its quest for search engine optimization through the creation of new technologies, which not only improves its search algorithms but also refines its search functions for users, doing it in a manner that makes it a perpetrator of primary copyright infringement or an invaluable facilitator for Internet functionality? How should the balance of interests in the treatment of creative works be recalibrated in the face of changes in search engine technology and operations, and the disputes that have arisen within the last decade in the context of the digital age and its needs? Using Google as a case study, this paper will look at the two main areas of dispute over the operations of information locator tools and services that either threatens search engine functionality and efficiency or weakens copyright holders’ exclusive rights. It proposes a concerted set of solutions through a reassessment and amendment of copyright law to optimize the social benefits and objectives of both the copyright regime and technological innovations in the electronic model of information archiving, indexing and delivery. A fair distribution of responsibilities and allocation of rights and liabilities will be suggested. In the process, due consideration will be given to both public and private interests, with the former taking precedence; while the recommended solutions will be made within the currently outdated framework for Internet intermediary protection (i.e. safe harbor laws) and exceptions (i.e. specific statutory exemptions and the general fair use defense) under the existing copyright regime. Thus, the proposed changes will be far reaching without being too radical a departure from current law, an evolution that will likely be more acceptable and realistic a solution to the problem.This paper is published in two parts. Part One of this paper published in the previous edition of the CLSR at [2011] 27 CLSR 110–131 dealt with the challenges to the copyright regime posed by the operations and technology behind the Google Images Search Engine, while Part Two will assess the benefits of the Google Books Search Project visàvis the effects it will have on the scope of copyright protection. Recommendations are made to copyright law to accommodate both functions while generally preserving the main objectives of copyright protection.